Time course of lymphocyte repopulation after dimethyl fumarate-induced grade 3 lymphopenia: contribution of patient age. (May 2019) - Briner, Myriam; Bagnoud, Maud; Miclea, Andrei; Friedli, Christoph; Diem, Lara; Chan, Andrew; Hoepner, Robert; Salmen, Anke
Background: Dimethyl fumarate (DMF) is licensed for treatment of relapsing–remitting multiple sclerosis (RRMS). DMF can induce lymphopenia, which is assumed to increase the risk for opportunistic infections like progressive multifocal leukoencephalopathy. Our goal for this work was to estimate the frequency of grade 3 lymphopenia in DMF-treated patients with RRMS and to characterize patient-sided factors influencing the time course of lymphocyte repopulation after DMF withdrawal. Material and methods: A single-center retrospective data analysis was performed at University Hospital Bern, Switzerland. Patients with DMF treatment were analyzed for lymphocyte counts. Demographic factors were statistically analyzed in grade 3 lymphopenic patients. Results: We estimated a grade 3 lymphopenia frequency of 11/246 (4.5%), corroborating previous studies. In all patients, lymphocytes recovered to values ⩾800/µl within 0.5 years. Multivariate linear regression analysis unmasked older age as being associated with a longer duration of repopulation. Conclusion: Considering the aging population, our findings warrant further investigations of DMF-induced lymphopenia.